2004
DOI: 10.1103/physrevlett.93.097202
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observation of Large Electronic Domains with Memory Effect in Doped Manganites

Abstract: We use a spatially resolved, direct spectroscopic probe for electronic structure with an additional sensitivity to chemical compositions to investigate high-quality single crystal samples of La(1/4)Pr(3/8)Ca(3/8)MnO3, establishing the formation of distinct insulating domains embedded in the metallic host at low temperatures. These domains are found to be at least an order of magnitude larger in size compared to previous estimates and exhibit memory effects on temperature cycling in the absence of any perceptib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
66
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 91 publications
(70 citation statements)
references
References 12 publications
4
66
0
Order By: Relevance
“…This is in agreement with a unified picture pointing toward a "physics" of manganites over two different correlation lengths, namely, one at the atomic level, where the interaction is basically driven by the hopping integral, and the other at the nanoscale/ mesoscale, dominated by the interactions among domains belonging to different competing phases. In many mixed-valence manganite compounds, the occurrence and the magnitude of CMR peaks at the insulator to metal transition basically depend upon the small scale site-site interactions (25), although PS is also observed and plays a role (26,27). The DE mechanism (1) and the interplay with the JT distortion appear to capture the essence of this phenomenon.…”
Section: Significancementioning
confidence: 99%
“…This is in agreement with a unified picture pointing toward a "physics" of manganites over two different correlation lengths, namely, one at the atomic level, where the interaction is basically driven by the hopping integral, and the other at the nanoscale/ mesoscale, dominated by the interactions among domains belonging to different competing phases. In many mixed-valence manganite compounds, the occurrence and the magnitude of CMR peaks at the insulator to metal transition basically depend upon the small scale site-site interactions (25), although PS is also observed and plays a role (26,27). The DE mechanism (1) and the interplay with the JT distortion appear to capture the essence of this phenomenon.…”
Section: Significancementioning
confidence: 99%
“…The calculated density of electrons n versus chemical potential µ for a one-dimensional model has shown a clear discontinuity in n at a particular value of µ, indicating a PS [7,8] since in general electronic PS results in the pinning of µ. Indeed, electron microscopy studies have revealed inhomogeneous spatial images in which the FM charge-disordered and AFM CO microdomains coexist [9,10,11]. However, it has been unclear whether they are driven by (intrinsic) tendency toward electronic PS or triggered by (extrinsic) chemical inhomogenity.…”
Section: Introductionmentioning
confidence: 99%
“…A possible interpretation of the result is that the mesoscopic FM region is itself inhomogeneous at the nanoscale with coexisting metallic and charge-ordered regions. A final example of mesoscale electronic inhomogeneities is from the experiments of Sarma et al (2004), who used photoemission spectromicroscopy which has the advantage of spatially resolving the local metallic/non-metallic nature and simultaneously determining the local chemical composition with a resolution of approximately 0.5 mm. Using this technique, they studied La 0.25 Pr 0.375 Ca 0.375 MnO 3 .…”
Section: (A ) Signatures Of Electronic Inhomogeneitiesmentioning
confidence: 99%